Socio-economic and environmental barriers to increased agricultural production: New evidence from central Thailand. (June 2021) - Apipoonyanon, Chidchanok; Szabo, Sylvia; Tsusaka, Takuji W; Leeson, Kevin; Gunawan, Endro; Kuwornu, John KM
Thailand's agricultural production has played a major role in enhancing the sustainability of domestic food supplies and successful international exports. However, agricultural production and farm productivity remain relatively low, especially in rapidly ageing high out-migration areas and among small-scale farmers. In this study, we use new household survey data from Prachinburi Province to examine the probability of facing six specific barriers to agricultural production. Data were analysed using descriptive statistics and a series of logistic regressions to identify the determinants. The results show that age of household head, off-farm income, farm size, and farm type were all associated with the likelihood of different productivity barriers. Gender of household heads was found to be associated with the probability of farm labour shortage, with female-headed households being at a disadvantage. We recommend that policies should be formulated to address these significant factors in order to overcome or circumvent the different barriers and enhance the livelihoods of the local population.